(untitled) (Journal of Parents and Teachers, 2026)
Drawing on Richard Paul’s book *Critical Thinking*, the author proposes a comparative analysis between what the book refers to as ‘didactic theory’ (DT) and, on the other hand, ‘critical theory’ (CT). Critical thinking, as noted, goes beyond the learning of externally provided content; rather, it involves a learning process in which the child takes centre stage. In line with this, a wide range of strategies are proposed to develop this critical thinking, accompanied by activities to be carried out in the classroom.